BRCA2 mutations in familial breast cancer with prostate cancer: a case report and literature review - Liu, Zhengsheng; Huang, Qianhao; Ding, Meixuan (Frontiers in Oncology, 2024)
Prostate cancer (PCa) is the second most common tumor in men globally. Its etiology has been attributed to multiple factors, including age and ethnicity, with family history identified as a significant risk factor. The role of family history in prostate cancer risk appears to be more extensive than previously thought, with evidence suggesting that prostate cancer and breast cancer may occur concurrently within families. BRCA2 mutations have been linked to an increased risk of prostate cancer, particularly in patients diagnosed with early-onset disease. It is estimated that BRCA2 mutations account for approximately 5% of familial prostate cancer cases. It is noteworthy that cases of prostate cancer in patients with BRCA2 mutations are rare in clinical practice. Here we report a case of prostatitis carcinoma with a mutation in the BRCA2 gene in a patient who underwent robotic-assisted radical prostatectomy for prostatitis carcinoma after medication was not effective. Genetic testing of him, his son, and his daughter showed that they all had mutations in this gene, and it is noteworthy that the type of BRCA2 mutation in his son has never been reported before, which is rare in clinical practice.